Off-label use of fixed-dose combination of tramadol and dexketoprofen in primary health care. Evidence-based or cause for concern? - Montserrat Viñas-Bastart; Míriam Oms-Arias; Àfrica Pedraza-Gutiérrez; Irene Lizano-Díez; Eduardo L. Mariño; Pilar Modamio Charles (Fundación Pharmaceutical Care España, 2022)
Introduction: The use of the fixed-dose combination of tramadol/dexketoprofen in Spain and in other countries has increased considerably. The authorized therapeutic indication for this medicinal product is the short-term symptomatic treatment of moderate to severe acute pain in adult patients. The objective of this study was to describe the pattern of use of tramadol/dexketoprofen in the field of primary health care. Method: A cross-sectional, descriptive and multicenter study was carried out. The study population included all patients from a Primary Care Department (53 Primary Care teams) with an active prescription of tramadol/dexketoprofen on March 28, 2018. The target population was those patients who were prescribed tramadol/dexketoprofen. dexketoprofen for >20 days. Results: A total of 176 patients had an active prescription for tramadol/dexketoprofen. All patients (100%) had a duration of treatment greater than 5 days and 72.7% (N=128) greater than 20 days. The mean duration of treatment was 14±160.9 days in patients who had less than 20 days of treatment and 224±160.8 days in patients who had more than 20 days of treatment. 35.1% of the patients were treated with >2 pain medications and concomitantly with tramadol/dexketoprofen. The general practitioner initiated 65.6% of the prescriptions. Conclusions: The fixed-dose combination of tramadol/dexketoprofen was frequently used off-label, according to the product characteristics and the available scientific evidence. This study warns about the potential risks associated with the use of this drug in clinical practice, such as lack of effectiveness and/or the appearance of adverse effects.